EFFECT OF CHIPPING ON THE SPILLAGE OF YIELD ELEMENTS AND LEAF SURFACE FORMATION IN COTTON (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In this article, the shedding of crop elements at different seedling thicknesses in cotton, the factors affecting the shedding, especially the methods of weeding, the effect of climate, agrotechnical factors are explained.